2018
DOI: 10.1002/mnfr.201700679
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Oligosaccharides as Promising Antivirals

Abstract: Human milk oligosaccharides (HMOs) are diverse unconjugated carbohydrates that are highly abundant in human breast milk. These glycans are investigated in the context of exhibiting multiple functions in infant growth and development. They seem to provide protection against infectious diseases, including a number of poorly manageable viral infections. Although the potential mechanism of the HMO antiviral protection is rather broad, much of the current experimental work has focused on studying of HMO antiadhesiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(80 citation statements)
references
References 135 publications
0
78
0
2
Order By: Relevance
“…In vitro studies have reported that Bifidobacteria and Lactobacillus are able to inhibit RV infection [2,37], for example by interfering in the adhesion step. In this regard, it may be possible that glycans or other molecules found on the surface of the bacteria interact with the virus, therefore blocking the infection, similar to oligosaccharides present in breastmilk [70,71] and infant formula [13].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have reported that Bifidobacteria and Lactobacillus are able to inhibit RV infection [2,37], for example by interfering in the adhesion step. In this regard, it may be possible that glycans or other molecules found on the surface of the bacteria interact with the virus, therefore blocking the infection, similar to oligosaccharides present in breastmilk [70,71] and infant formula [13].…”
Section: Discussionmentioning
confidence: 99%
“…HMOs prevent the attachment of pathogenic bacteria by serving as soluble glycan receptor decoys. It has been reported that HMOs resemble structures of viral receptors and prevent adherence to cells, therefore preventing infection [81][82][83]. A number of studies have documented that HMOs play an important role in preventing infant gastrointestinal and respiratory tract infections [84,85].…”
Section: Human Milk Oligosaccharidesmentioning
confidence: 99%
“…Branching can be linear or branched through bonds b1-3 or b1-6. The sequence can be further modified by the addition of Fuc and/or SA monosaccharides through alpha 1-2,3,4 and alpha 2-3,6 bonds due to the action of fucosyltransferases and sialyltransferases [6].…”
Section: Introductionmentioning
confidence: 99%
“…further modified by the addition of Fuc and/or SA monosaccharides through alpha 1-2,3,4 and alpha 2-3,6 bonds due to the action of fucosyltransferases and sialyltransferases [6]. Human milk contains three major HMO types: neutral, neutral N-containing and acid.…”
Section: Introductionmentioning
confidence: 99%